ORGANIZATIONAL AND LEGAL FOUNDATIONS OF THE PROSECUTORIAL ACTIVITY: A COMPARATIVE-LEGAL ANALYSIS - DJUMAYEV Shokhjakhon Begimqul ugli (Western European Studies, 2025)
This article provides a comprehensive comparative-legal analysis of the organizational and legal foundations of prosecutorial activity, emphasizing the need to modernize and harmonize the legal framework governing the prosecutor’s office of Uzbekistan. The study highlights the importance of strengthening prosecutorial oversight to ensure the precise and uniform execution of laws, particularly within the context of the New Uzbekistan Development Strategy (2022–2026). Special attention is given to the legal status, functions, and normative bases regulating the activities of prosecution bodies in Uzbekistan and selected foreign countries, including Russia, Ukraine, and Kazakhstan. The article argues that international treaties, which form an integral part of the national legal system under the renewed Constitution, must be formally recognized as a legal basis of prosecutorial activity. The author further proposes expanding the subject of prosecutorial review to include compliance not only with national legislation but also with international treaties ratified by Uzbekistan. Empirical data from a survey of more than 5,400 prosecutors reinforces the relevance and necessity of these reforms. The findings ultimately justify specific legislative amendments aimed at improving the effectiveness, transparency, and international compatibility of prosecutorial oversight
Keywords: prosecutorial supervision; legal framework; organizational foundations